Saṅghabhadra's arguments for the existence of an intermediate state (antarābhava) between biological death and rebirth as translated by Xuanzang (602?-664 ce) - Brewster, Ernest B. ca. 20./21. Jh. (Religious studies, 2024)
The Buddhist doctrine of transmigration (saṃsāra) offers a coherent model of a cycle of existence wherein a sentient being continues throughout life, survives death, traverses the afterlife, and is, sooner or later, reborn, thus inaugurating another lifecycle as a new life-form. The Buddhist tenets of no-self (anātman) and impermanence, however, deny the possibility of a self, soul, or any form of spiritual substance that persists throughout the cycle of transmigration. This article examines the argumentation developed by the Indic Buddhist philosopher, Saṅghabhadra (fl. fifth- century ce), as part of his effort to reconcile the doctrines of no-self and karmic continuity. In his *Nyāyānusāraśāstra and the *Samayapradīpikāśāstra, two seminal, yet vastly understudied, doctrinal treatises of Sarvāstivāda Abhidharma Buddhism that survive only within the translation corpus of the Sinitic scholar-monk Xuanzang (602?-664 ce), Saṅghabhadra defines the antarābhava, the "intermediate state of existence", as the interstitial space and interim time-period existing between the locus wherein the sequentially reproducing psychic constituents of an individual sentient being, including consciousness, desert the no-longer viable body at the moment of biological death, and the locus wherein these psychic constituents become associated with a new gross physical body in the form of a new viable embryo at the moment of rebirth. By instantiating the antarābhava as an actual interval with real extension in space and time, necessarily traversed by the vast majority of sentient beings after dying in order to reach the next gross physical body, Saṅghabhadra provides, for Sarvāstivāda Abhidharma Buddhism, a rigorous account for how karma is transmitted, via the psychic constituents of a sentient being, beyond biological death into future lives, as well as future afterlives.